Assessment of TEMPO as a thermally activatable base generator and its use in initiation of thermally-triggered thiol-Michael addition polymerizations. Issue 32 (20th July 2018) - Zhang, Xinpeng; Huang, Sijia; Podgórski, Maciej; Han, Xun; Claudino, Mauro; Bowman, Christopher N.
Abstract : We present a thermally initiated thiol-Michael reaction based on initiation via the temperature-dependent thiol-TEMPO oxidation–reduction reaction. Abstract : We present a thermally initiated thiol-Michael reaction based on initiation via the temperature-dependent thiol-TEMPO oxidation–reduction reaction. In the presence of a thiol, 2, 2, 6, 6-tetramethylpiperidine-1-oxyl (TEMPO, p K a = 5.5) is reduced to produce a much stronger base, i.e., tetramethylpiperidine (TMP, p K a = 11.4) in a temperature dependent process. This oxidation–reduction process is dramatically accelerated at elevated temperature, which allows for thermally controlled initiation of the base-catalyzed thiol-Michael addition reaction and potentially other base-catalyzed reaction systems. Several critical factors that affect base generation from TEMPO reduction were investigated via systematic variation of reaction conditions including the solvent, temperature, and the thiol type and concentration. The highly temperature-dependent attributes of this redox reaction were demonstrated in various thiol-TEMPO based systems and were further utilized to thermally control thiol-Michael polymerizations under different heating conditions. The strong amine species, TMP, formed at elevated temperatures from the TEMPO-thiol interaction combined with high temperature, enables rapid formation of thiol-Michael-based polymer networks and large scale material preparation without any detrimental effects often associated with highly exothermic polymerizations. This novel approach to develop thermally-initiated thiol-Michael polymer networks is unique, versatile and robust, resulting in wide utility in applications such as facile handling of highly reactive resins, bulk material preparation, pH sensitive materials construction, and composite/macro-particle synthesis.